2012
DOI: 10.1371/journal.pone.0040297
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function and Falls in Older Adults: New Findings from a Five-Year Prospective Study Link Fall Risk to Cognition

Abstract: Background Recent findings suggest that executive function (EF) plays a critical role in the regulation of gait in older adults, especially under complex and challenging conditions, and that EF deficits may, therefore, contribute to fall risk. The objective of this study was to evaluate if reduced EF is a risk factor for future falls over the course of 5 years of follow-up. Secondary objectives were to assess whether single and dual task walking abilities, an alternative window into EF, were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
290
3
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(324 citation statements)
references
References 50 publications
21
290
3
10
Order By: Relevance
“…Deficits in executive function have been identified as a particular risk factor related to an increase in falls rates [1][2][3]. Two systematic reviews showed that most studies had used the Trail Making Test (TMT) to assess executive function [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficits in executive function have been identified as a particular risk factor related to an increase in falls rates [1][2][3]. Two systematic reviews showed that most studies had used the Trail Making Test (TMT) to assess executive function [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The TMT examines scanning, visuo-motor tracking, divided attention and cognitive flexibility [4], and is regarded as a standard measurement of executive function [5]. Furthermore, processing speed, abstract reasoning and attention, which are related to executive function [1][2][3], have been associated with the fate of falls. Cognitive training with a focus on executive function has recently been included in exercise studies for people with dementia [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the loading response phase, the patients with PD exhibited increases in Area 1 that scaled with increases in cognitive decline (UPDRS1). Cognitive decline is another independent risk factor for falls (Herman et al, 2010;Mirelman et al, 2012). Gait disorders and falls are more prevalent among demented patients than non-demented subjects, and there is a direct relationship between the severity of cognitive impairment and increased gait abnormalities (Amboni et al, 2013;van Iersel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Outros estudos mostraram que idosos com prejuízos nas funções executivas são mais suscetíveis a quedas (Holtzer et al, 2007;Alexander e Hausdorff, 2008;Mirelman et al, 2012). Em um estudo prévio, Herman et al (2010) relataram que idosos saudáveis com melhor desempenho nas funções executivas apresentavam menor probabilidade de cair quando comparados com aqueles que tiveram pontuação menor nos testes neuropsicológicos.…”
Section: Alterações Cognitivas Decorrentes Do Envelhecimento Que Afetunclassified
“…flexibilidade mental e memória de trabalho (Stuss et al, 2007), com repercussões negativas sobre a independência e qualidade de vida dos idosos (Yogev-Seligmann et al, 2008;Herman et al, 2010;Mirelman et al, 2012), a melhora por si só destas funções já pode ser considerada clinicamente relevante para a funcionalidade dos idosos. Estudos que utilizaram outros recursos terapêuticos como fármacos e treinamento para melhorar a função cognitiva de idosos, encontraram efeitos positivos no controle de equilíbrio e redução de quedas (Gillespie et al, 2009;Montero-Odasso et al, 2009).…”
Section: O Potencial Da Utilização De Videogame Para a Melhora Do Equunclassified